MENGENAL DAN MENCEGAH DISFAGIA MELALUI MODIFIKASI MAKANAN DAN LATIHAN MENELAN - Devina Wiatanti; Yovi Yolandari; Fathyanidaa Jasmine Rihhadatul'aisy; Laily Nur Jannah; Shiane Hanako Sheba (JURNAL PENGABDIAN KEPADA MASYARAKAT (ADI DHARMA), 2025)
Dysphagia is a swallowing disorder commonly experienced by older adults as well as patients with neurological disorders and chronic diseases. This condition may lead to various complications, including aspiration, malnutrition, and dehydration. The management of dysphagia is not limited to medical treatment but also requires a comprehensive non-pharmacological approach, including education, modification of food and fluid textures, and swallowing exercises. Food texture modification is performed to match the patient’s swallowing ability, thereby ensuring a safer and more effective eating process. Education plays an important role in improving patients’ understanding of safe eating practices, proper body positioning during meals, and adherence to recommended dietary guidelines. In addition, swallowing exercises are implemented to strengthen the muscles involved in the swallowing process and to improve coordination. Consistent application of these interventions is expected to reduce the risk of aspiration, enhance nutritional intake, and improve the quality of life of patients with dysphagia